Co-adaptation of Streptococcus mutans to simulated microgravity and silver nitrate - Fernander, Mizpha C.; Spurgeon, Kelyah; Graves, Jada; Guess, Wynter; Miller, Jordan; Mangum, Chanell; Graves, Joseph L.; Thomas, Misty D. (Frontiers in Astronomy and Space Sciences, 2023)
To sustain life on extended space missions, it is essential to maintain clean potable water. NASA currently uses iodine as the primary biocide in the potable water dispenser on the International Space Station and has recently proposed a potential switch to silver-based antimicrobials. Streptococcus mutans is the primary etiological agent of dental caries, part of the normal oral flora, and would endure direct exposure to water from the potable water dispenser. In our previous work, we examined the 100-day adaptive response of Streptococcus mutans to simulated microgravity (sMG). Here, we examined the evolutionary co-adaptation of S. mutans under sMG and silver nitrate (AgNO3) to evaluate the consequences of using silver as a primary biocide in space and the impact on the evolution of microbes from the oral microbiome. To do this, we adapted four populations of S. mutans under sMG and co-adapted four populations in simulated microgravity and silver nitrate using high-aspect ratio vessels for 100 days. Genomic analysis at multiple time points showed that S. mutans in sMG evolved variants consistent with our previous findings (SMU_1307c and SMU_399) while also acquiring novel mutations in the glutathione reductase gorA. The co-adapted populations showed mutations specific for the environment in ciaH/R, PBP1a, trkA, and trkB. We also assessed virulence phenotypes, and while simulated microgravity increased antibiotic susceptibility, sucrose-dependent adhesion, and, in some populations, acid tolerance, co-adaptation to silver nitrate reversed these effects. Overall, these data show that the use of silver as a biocide in simulated microgravity can evolve strains with novel genotypic and phenotypic traits that could alter virulence.